Perceptions and Economic Losses of Foot and Mouth Disease to Beef Cattle Farmers in Bantul Regency, Yogyakarta - Putra, D. W.; Kusumastuti, T. A.; Andarwati, S.; Panjono; Guntoro, B. (Faculty of Animal Science, IPB University, 2024)
The objectives of this study were to measure the level of farmers’ perceptions on psychological, socio-cultural and economic aspects, and to analyze the economic losses during foot and mouth disease (FMD) outbreaks. This study was conducted in Bantul District, Yogyakarta, during the period of July-September 2023. A total of 148 farmers affected by FMD were surveyed by a purposive sampling method using a questionnaire and the data were analyzed using the ordinal logistic regression method. The result showed that farmers’ perceptions of FMD outbreaks of psychological, socio-cultural and economic attributes were in the high category. The majority of farmers experienced low economic losses (47.30%). Age and livestock ownership (p<0.01), formal education, and informal education (p<0.1) had a positive effect on the level of farmers’ economic losses, while only farming experience (p<0.01) had a negative effect. Pseudo R-Square value of 33.9% or the level of economic losses, is influenced by farmers’ age, farming experience, livestock ownership, as well as formal and informal education. Reaction in the field of opportunity: the highest level of economic losses in the low category is 0.997%. This study shows that FMD handling carried out by farmers is good enough to prevent the impact of large economic losses on cattle farmers in Bantul Regency.